EPCT-06. Phase I study of ribociclib and everolimus post-radiotherapy in children with newly diagnosed diffuse intrinsic pontine glioma (DIPG) and high-grade glioma (HGG): Updated report from the COllaborative Network for NEuro-Oncology Clinical Trials (CONNECT). (3rd June 2022) - Lazow, Margot A; DeWire, Mariko; Campagne, Olivia; Leach, James L; Fuller, Christine; Kumar, Shiva Senthil; Stanek, Joseph; de Blank, Peter; Hummel, Trent R; Pillay-Smiley, Natasha; Salloum, Ralph; Stevenson, Charles B; et al.
Abstract: BACKGROUND: Dual inhibition of CDK4/6 and mTOR in DIPG and pediatric HGG has strong biologic rationale, given prevalent genetic alterations resulting in upregulated cell cycle and PI3K/mTOR pathways in these diseases, as well as non-overlapping agent toxicities. This study sought to evaluate safety/tolerability and determine the recommended phase 2 dose (RP2D) of ribociclib and everolimus among children with newly diagnosed DIPG and HGG post-radiotherapy. METHODS: Patients were enrolled according to a Rolling-6 design and received oral ribociclib and everolimus once daily for 21 and 28 days, respectively, starting 2-4 weeks post-completion of radiotherapy. All HGG and biopsied DIPG patients were screened for RB protein presence by immunohistochemistry. Pharmacokinetics and survival data were analyzed. RESULTS: Nineteen patients enrolled (median age: 8 years [range: 2-18]). Three patients enrolled at each of dose levels 1 and 2 without dose-limiting toxicities (DLTs). Thirteen patients enrolled at dose level 3, with one patient experiencing a DLT (grade 3 infection). One patient came off therapy prior to cycle 9 due to cardiac toxicity. The most common grade 3/4 toxicities were neutropenia (33%), leucopenia (17%), and lymphopenia (11%). Steady-state everolimus exposures in combination were 1.9±0.9-fold higher than single-agent administration. Median overall survival (OS) for 15 patients with DIPG was 13.9 months, with 12-, 24-, and 36-month OS of 53.3%, 38.9%, and 38.9%. Median event-free survival for four patients with HGG was 10.5 months. Among patients with tumor molecular profiling, two longer survivors (OS: 20, >37 months) had evidence of cell cycle upregulation with CDKN2A/B deletion and CDK4 overexpression identified. CONCLUSIONS: The combination of ribociclib and everolimus was well-tolerated post-radiotherapy in children with newly diagnosed DIPG and HGG, with a RP2D of ribociclib 170 mg/m2 days 1-21 and everolimus 1.5 mg/m2 days 1-28. Results will inform a molecularly-guided phase II study currently underway to evaluate efficacy.